1,3-Thiazine, 1,2,3,4-Dithiadiazole, and Thiohydrazide Derivatives Affect Lipid Bilayer Properties and Ion-Permeable Pores Induced by Antifungals - Zakharova, Anastasiia A.; Efimova, Svetlana S.; Yuskovets, Valeriy N.; Yakovlev, Igor P.; Sarkisyan, Zara M.; Ostroumova, Olga S. (Frontiers in Cell and Developmental Biology, 2020)
Over the past decade, thiazines, thiadiazoles, and thiohydrazides have attracted increasing attention due to their sedative, antimicrobial, antiviral, antifungal, and antitumor activities. The clinical efficacy of such drugs, as well as the possibility of developing resistance to antimicrobials, will depend on addressing a number of fundamental problems, including the role of membrane lipids during their interaction with plasma membranes. The effects of the eight 1,3-thiazine-, 1,2,3,4-dithiadiazole-, and thiohydrazide-related compounds on the physical properties of model lipid membranes and the effects on reconstituted ion channels induced by the polyene macrolide antimycotic nystatin and antifungal cyclic lipopeptides syringomycin E and fengycin were observed. We found that among the tested agents, the fluorine-containing compound N'-(3,5-difluorophenyl)-benzenecarbothiohydrazide (C6) was the most effective at increasing the electric barrier for anion permeation into the hydrophobic region of the membrane and reducing the conductance of anion-permeable syringomycin pores. A decrease in the membrane boundary potential with C6 adsorption also facilitated the immersion of positively charged syringomycin molecules into the lipid bilayer and increases the pore-forming ability of the lipopeptide. Using differential scanning microcalorimetry, we showed that C6 led to disordering of membrane lipids, possibly by potentiating positive curvature stress. Therefore, we used C6 as an agonist of antifungals forming the pores that are sensitive to membrane curvature stress and lipid packing, i.e., nystatin and fengycin. The dramatic increase in transmembrane current induced by syringomycin E, nystatin, and fengycin upon C6 treatment suggests its potential in combination therapy for treating invasive fungal infections.